Determinan Transfer Pricing Pada Perusahaan Pertambangan Di Indonesia (Study Multy Years pada Perusahaan yang Terdaftar pada Bursa Efek Indonesia tahun 2019-2021) - Retno Kusumaningrum (LP2M, 2022)
This study was conducted to find out how to determine transfer pricing in mining companies listed on the IDX. The study used quantitative methods with purposive sampling, namely conditional sampling techniques. From the results of the study, it can be concluded that company size, Leverage Ratio, bonus mechanism, Intangible Assets, and Profitability partially have a significant effect on the company's transfer pricing, while Tunneling Incentives and Multinationality partially have no significant effect on the company's transfer pricing. Simultaneously, Company size, Leverage ratio, bonus mechanism, Tunneling Incentives, multinationality, intangible assets and profitability have a significant effect on the transfer pricing of Mining Companies in Indonesia which are listed on the IDX in a row during the 2015-2019 period.